Development and Evaluation of the TRIKON-S Model for Strengthening Social Skills in Early Childhood Education - Dian Tri Utami; Restu Nabila Nabila; Alucyana Alucyana; Yenni Yunita; Cahaya Ramadhanty; Jeffery bin Apdal (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Social skills in early childhood are an important foundation for the ability to interact, communicate, and adapt in social life. In the process of social interaction, children often experience simple conflicts such as fighting over toys, difficulty taking turns, differences of opinion, and emotional outbursts. However, conflicts in children are often ignored or resolved directly by teachers without giving children the opportunity to learn to resolve them independently. This study aims to develop the TRIKON-S (Transforming Interaction in Conflict-Social) model as a conflict resolution learning approach to strengthen the social skills of early childhood and to test its feasibility and effectiveness. The study used the Research and Development (R&D) method with the Borg & Gall model through ten stages of development. The research subjects consisted of 60 children aged 5–6 years in several PAUDs in Pekanbaru City. Data were collected through observation, interviews, documentation, and social skills assessment sheets, then analyzed using quantitative and qualitative approaches. The results showed that the TRIKON-S model was in the very feasible category based on expert validation. The implementation of the model proved effective in improving children's social skills, with an N-Gain value of 0.71 (high category) and a significant t-test result (p < 0.05). Children demonstrated improved communication, cooperation, empathy, responsibility, and self-control skills during the learning process. These findings confirm that social conflict can be transformed into meaningful learning experiences to strengthen the social skills of early childhood.